Kebijakan Kriminal Penanggulangan Tindak Pidana Pemerkosan di Transportasi Umum - Dwi Haryadi (Magister Administrasi Publik, 2012)
Criminal acts involving the perpetration of rape in public transportation vehicles which have become common these day, have caused a lot concern an anxiety in the general public. The root cause of such heinous acts can be traced t the disorientation of some section of society that is attributable to social disorganization, which in turn has undermined social control, individualism and materialism, rampant pornography, booze and porno-action, poor government oversight of public transport, among other factors. Resolving the problem calls for several measure, which among others should include, strengthening the penal code to empower stringent legal action against the perpetrators, and taking effective preventive measures to deal with multifaceted cause of social disorganization.